THE THIRD RENAISSANCE MOVEMENT IN UZBEKISTAN - Hojiyev Farhod Jumaboyevich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article examines the periods of rapid development in science and culture in Central Asia, specifically the First and Second Renaissance periods and their essence. It also addresses the activities, exemplary lives, and unique works of the great thinkers who lived and worked during those times. The article provides analytical insights into the glorious history of Mavarannahr, the gradual decline of science in the region, the processes leading to the end of statehood, and their causes and consequences. It offers relevant information on the scientific study of the great past, the lives and spiritual legacy of the scholars of the First and Second Renaissance periods, and the historical foundation for the Third Renaissance, as well as its relevance to real life, along with appropriate conclusions and suggestions.